Incidence of Injuries in Motorcyclists Practitioners of Trails - Sousa, Davi Leal; da Silva, Kelson Nonato Gomes; Ferreira, Eduardo; Morais, Flávio Rogério de Sousa (Revista Brasileira de Ortopedia, 2020)
Objective To investigate the incidence, mechanisms, types of injury, most affected anatomical regions, and factors leading to injuries in trail bikers.Methods This was an observational, retrospective study analyzing 47 trail bikers. Data were collected through application of a referenced morbidity survey (RMS), which included information on injuries and their mechanisms.Results The lesions with the highest incidence were abrasion and bruise. The most affected anatomical regions were the shoulders and knees. The most common injury mechanism was skidding or loss of traction.Conclusion Trail bikers are exposed to risk factors and, consequently, to falls; it is important to develop more protective equipment, especially for the shoulders and knees.
Keywords: sports; off-road motor vehicles; sports injuries; motorcycles